Call sign : Lightning - Messmore, Scott (Stackpole Books, 2017)
The U.S. Marine Corps' Air Naval Gunfire Liaison Companies--usually referred to as ANGLICOs--are the unsung heroes of the U.S. military. Small squads of these marines are inserted deep behind enemy lines to identify targets and direct fire from aircraft, ground artillery, and naval guns. They are among the best of the best, and their radio call sign "Lightning" is recognized throughout the military as the gold standard of qualification and capability